2011
DOI: 10.1038/onc.2011.242
|View full text |Cite
|
Sign up to set email alerts
|

Rack1 promotes epithelial cell–cell adhesion by regulating E-cadherin endocytosis

Abstract: E-cadherin and its cytoplasmic partners, catenins, mediate epithelial cell-cell adhesion. Disruption of this adhesion allows cancer cells to invade and metastasize. Aberrant activation of the Src tyrosine kinase disrupts cell-cell contacts through an E-cadherin/catenin-dependent mechanism. Previously we showed that Rack1 regulates the growth of colon cells by suppressing Src activity at G 1 and mitotic checkpoints, and in the intrinsic apoptotic and Akt cell survival pathways. Here we show that Rack1, partly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 59 publications
2
32
0
Order By: Relevance
“…We show that RACK1 is localized at the cell–cell contacts in Xenopus embryonic mesenchyme-like cells. This result is in agreement with previous reports showing that RACK1 is localized at cell–cell junctions in HT-29 human colon cancer cell line and mink Mv 1 Lu cells (Swaminathan and Cartwright, 2012; Mourton et al, 2001). We also show that in polarized Xenopus embryonic epithelial cells RACK1 co-localizes with ZO-1 at the apical cell–cell junction.…”
Section: Discussionsupporting
confidence: 94%
“…We show that RACK1 is localized at the cell–cell contacts in Xenopus embryonic mesenchyme-like cells. This result is in agreement with previous reports showing that RACK1 is localized at cell–cell junctions in HT-29 human colon cancer cell line and mink Mv 1 Lu cells (Swaminathan and Cartwright, 2012; Mourton et al, 2001). We also show that in polarized Xenopus embryonic epithelial cells RACK1 co-localizes with ZO-1 at the apical cell–cell junction.…”
Section: Discussionsupporting
confidence: 94%
“…Potentially, by regulating c-Src, RPTPa could control events in the endocytic pathway, given the implication of the former in epithelial E-cadherin endocytosis (Canel et al, 2010;Swaminathan and Cartwright, 2012) and in neuronal neurotransmitter receptor trafficking in neurons (Ohnishi et al, 2011).…”
Section: Functions Of Rptpa At the Epithelial Junctionsmentioning
confidence: 99%
“…It was also previously reported that Rack1 acts as a substrate and inhibitor of Src [5860], regulating cell growth through the inhibition of Src activity at G1 and mitotic cell-cycle checkpoints and cell survival pathways [6163]. Taken in consideration these premises, in 2011, it was addressed the effect of Rack1 on Src signaling and its function on E-cadherin-mediated cell–cell adhesions [64]. It was shown that Rack1 promotes cell–cell adhesion by stabilizing E-cadherin and catenins at cell–cell junctions and reduces invasive potential of colon carcinoma cells.…”
Section: Hakai In Response To Oncogenic Signaling Pathwaysmentioning
confidence: 99%